Afscheid van een moederbinding : uitdaging van Nieuw Lila aan het COC. - Branderhorst, Henk; Bussink, Ben; De Feyter, Pieter; Sikkel, Rijk-Jan; Swiebel, Joke; Tielman, Rob (Amsterdam : Nieuw Lila, 1969)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie